The performance of commodity trading advisors: A mean-variance-ratio test approach - BAI, Zhidong (Institutional Knowledge at Singapore Management University, 2013)
In this paper, we provide evidence that the mean-variance-ratio (MVR)test is superior the Sharpe Ratio (SR) test by applying both tests to analyze the performance of commodity trading advisors (CTAs). The findings show that while the SR test concludes that most of the CTA funds being analyzed are indistinguishable in their performance, the MVR statistic shows that some funds outperformed others. Moreover, the SR statistic indicates that one fund significantly outperformed another even when the difference between the two funds was insignificant or even changed directions over sub-periods. Conversely, the MVR statistic can detect such changes when they occur over sub-periods. In addition, we have conducted simulations to show that the MVR test possesses good power.